S91 Improved Lung Cancer Survival and Reduced Emergency Diagnoses Resulting from an Early Diagnosis Campaign in Leeds 2011. (19th November 2012) - Cheyne, L; Foster, C; Lovatt, V; Hewitt, F; Cresswell, L; Fullard, B; Fear, J; Darby, M; Robertson, R; Plant, PK; Milton, R; Callister, MEJ
Abstract : Background: Lung cancer survival in the UK lags behind other developed nations, and excess early deaths following diagnosis suggest advanced disease at presentation. Patients diagnosed with lung cancer following emergency presentation to hospital have poorer survival than those patients referred to outpatient clinic (1 year survival 9% vs 39% respectively). Leeds has an excess of lung cancer deaths per year compared with the rest of UK, and Leeds Teaching Hospitals NHS Trust (LTHT) sees the highest number of lung cancer cases nationwide. Methods: NHS Leeds and LTHT undertook a 12 month campaign to encourage earlier diagnosis of lung cancer comprising four key elements: a marketing communications campaign, a community education programme, a primary care educational programme, and a self request chest X-ray service. Outcome measures for the intervention year (2011) were compared to historical controls (2008–2010). Results: The number of community-ordered CXRs increased from 18, 909 per annum (2008–2010) to 29, 278 in 2011 (55% increase, p<0.0001). The 2011 figure includes 2, 515 patients who self-referred for CXR. Overall diagnoses of lung cancers rose by 8% in 2011 compared to 2008–2010 (mean±SD 44.9±8.6 vs 41.6±6.4 respectively, p=0.15). There was no significant change in stage of lung cancer or patient performance status at presentation (although the study was not powered to demonstrate this). The proportion of patients diagnosed with lung cancer following emergency presentation reduced from 32.9% (2008–2010) to 27.8% (2011, p=0.035). There was an increase in the proportion of lung cancer patients first seen in the fast-track lung cancer clinic following GP referral or CXR recall (39.3% in 2008–2010 compared to 46.6% in 2011, p=0.02). 180 day mortality (assessed in July 2012) was 44.7% for 2008–2010 and 40.4% in 2011 (p=0.10) and survival curves are shown below. Further mortality data will be available in late 2012. Conclusion: Improvements in survival and a reduction in emergency admissions are likely to reflect increase referral of symptomatic patients for CXR. Further analysis of Cancer Registry survival data will allow comparison with other UK centres over the same time period. No stage or performance status shift was seen.